Gente de toda parte foi ver o ex-metalúrgico virar presidente da República : a narrativa da posse de Lula na Folha de S. Paulo e em O Globo - Holzbach, Ariane Diniz (2010)
The main objective of this research is to analyze the media behavior during the Brazilian investiture ceremony. Hence, we are going to analyze the news of the first investiture ceremony of Luiz Inácio Lula da Silva, which happened on January, 1st, 2003 and was published in the two most sold newspapers of Brazil: Folha de S. Paulo and O Globo. The analyzed corpus consists of 86 pieces of news 35 of O Globo and 48 of Folha de S. Paulo that were published on January, 2st, 2003. All the news refer to the ascension of Lula as president. The investiture ceremony is a singular moment of the representative democracy because it holds back the conflicts that normally take part in our political life, and the media is fundamental in this context. The exception of this ritual can be viewed as a symbolic window which helps us to see some social elements that are not explicit during the every-day life. Generally, when the media reports those facts, two discursive models can be prioritized: the informative model, which are more common and the information is the protagonist; and de narrative model, which prioritizes the history of the event, not their details. Therefore, this work analyzes the general default of both newspapers coverage and three of the representative democracy inherent characteristics that can be observed in the news: the representative mandate, the power alternation and the popular character. We can observe that each newspaper has adopted different kinds of discursive models, and it is a reflex of each one s history and development. Besides, Folha has an informative coverage, O Globo has preferred the narrative model.